The dyslexic student’s experience of education - Thompson, L. S. (South African Journal of Higher Education, 2021)
This article explores the lived experiences of students with dyslexia at public universities. The researcher conducted a qualitative phenomenological study using Interpretative Phenomenological Analysis and collected data via semi-structured, in-depth interviews from university students who have all been formally diagnosed with dyslexia. Three main themes emerged from the data: (1) barriers to learning (2) coping strategies employed by dyslexic students, and, (3) the support offered by university structures. The findings indicated that dyslexic students experience a significant amount of anxiety at university, and this is often linked to the lack of societal awareness of dyslexia by academic staff. The findings also revealed that although dyslexic students face barriers to learning that they must overcome, they are equipped with self-taught coping mechanisms. The main conclusion that can be drawn from this study is that if dyslexic students receive the necessary and appropriate support, they can be as successful as their non-dyslexic peers.